ANALISIS PENGARUH CURAH HUJAN TERHADAP EROSI PADA JALAN TANJUNG BARANGAN KOTA PALEMBANG - Permatasari, Rosmalinda; Andayani, Reni; Rohmansyah, Hamdan Nur; Marlina, Ayu (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2025)
Jalan Tanjung Barangan is located in Kecamatan Bukit Baru, Palembang City, which hydrologically is included in the Lambidaro river basin (DAS). Erosion occurred at several points along the road at Tanjung Barangan, with the dominant land use at the research location being housing. At this location, a landslide disaster occurred on December 25 2021. The aim of this research was to determine the value of erosivity, the amount of soil eroded per year and the level of erosion hazard using the USLE (Universal Soil Loss Equation) calculation method. Samples were taken at 3 points on Jalan Tanjung Barangan where sieve and soil erodibility tests will be carried out in the laboratory. Furthermore, for the purposes of calculating erosion values, slope level, vegetation cover factors, secondary data was also collected in the form of rainfall data for 5 years at two rain post points, namely SMB II and Tanjung Barangan obtained from BMKG and the Ministry of PUPR BBWS Sumatra VIII, slope map slopes and topographic maps that will be analyzed together with the samples. The research found that the erosivity value of rain in the Lambidaro watershed was 235,374 kj/yr, eroded soil in the Tanjung Barangan area of Palembang City was 26.42 tons/yr/ha and the level of erosion hazard that occurred at the research location was class II with a mild classification, namely eroded soil. as much as 15-60 tons/year/ha.